Pengendalian Internal Persediaan Barang Pada Toko Tembakau Bumi Tobacco - Tedi Luay; Rifa Maulana; Dwi Epty Hidayaty (Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine the effect of the quality of human resources, the importance of performance on employee performance at Bumi Tobacco. Many factors affect employee performance, but factors that are rarely measured are the importance of performance and the quality of human resources. This study used a quantitative approach with data collection techniques using a questionnaire. The number of samples in this study were 5 respondents. The data analysis technique used in this study uses descriptive data. The results of the study showed that the quality of human resources had a significant positive effect on the importance performance of Bumi Tobacco SMEs. The Quality of Human Resources has a significant positive effect on Employee Performance and Satisfaction at Bumi Toacco. Importance performance has a significant positive effect on employee performance and satisfaction at Bumi Tobacco. The findings show that Bumi Tobacco's performance in key areas is significantly influenced by the quality of its human resources. At Bumi Tobacco, the quality of human resources significantly improves employee performance and satisfaction. Critical performance has a very beneficial impact.